2015
DOI: 10.1016/j.wem.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Avalanche Safety Equipment of Backcountry Users: Current Trends and Perceptions

Abstract: Standard avalanche safety practices, including taking an avalanche safety course and carrying standard equipment, remain the most common safety practices among backcountry users in the Wasatch and Tetons. Snowshoers remain an ideal target for outreach to increase avalanche awareness and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Overall proportions of survey participants carrying standard safety gear, recreating with companions, and having previously participated in avalanche preparedness courses were similar to numbers previously reported from surveys conducted in Utah, Wyoming, and Italy in 2006, 2011, and 2014. 9 11 This study differs from previous reports in that it sought associations of safety practices with participant background information, such as demographics and level of expertise, in a North American setting. In 2014, Procter et al reported the results of their survey of safety practices in Italy, which evaluated associations between safety behaviors and additional background information of backcountry recreationists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall proportions of survey participants carrying standard safety gear, recreating with companions, and having previously participated in avalanche preparedness courses were similar to numbers previously reported from surveys conducted in Utah, Wyoming, and Italy in 2006, 2011, and 2014. 9 11 This study differs from previous reports in that it sought associations of safety practices with participant background information, such as demographics and level of expertise, in a North American setting. In 2014, Procter et al reported the results of their survey of safety practices in Italy, which evaluated associations between safety behaviors and additional background information of backcountry recreationists.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a 2014 survey of backcountry snow sport recreationists in Utah and Wyoming, the majority of participants reported carrying standard safety equipment (beacon, probe, and shovel) and having previously attended an avalanche safety course. 11 Despite survey findings of relatively high rates of performance of safety practices, Jekich et al reported in 2016 that avalanche fatalities have steadily risen over the last 6 decades. 12 They suggest that this is likely due to overall rising rates of participation in backcountry recreation, which, by definition, exposes recreationists to higher avalanche risk than in-bounds snow sports.…”
Section: Introductionmentioning
confidence: 99%
“…However, many user groups (off-piste recreationists, snowshoers, ice climbers) do not. 6 ,7,10,11 In addition, many avalanche fatalities occur close to the secured ski areas. For these situations, the RECCO Rescue System potentially offers a second option to transceivers for locating these victims.…”
Section: Discussionmentioning
confidence: 99%
“…social cues). Safety equipment (beacons, airbag packs) meant recovery from an accidents increased survival/injury rates and so the accident may not appear in accident data (Haegeli et al, 2014;Ng et al, 2015).…”
Section: Analysis Biasmentioning
confidence: 99%